Neuropathic Pain in Syringomyelia: A Case Report and Comprehensive Review of Clinical Management - Rizaldy Taslim Pinzon; Bernadeta Amaya; Stefanus Erdana Putra (Universitas Pelita Harapan, 2026)
Introduction: Syringomyelia is an uncommon chronic spinal cord disorder characterized by the formation of a fluid-filled cavity (syrinx) within the neural parenchyma. This condition leads to progressive neurological impairment and severe neuropathic pain. This case report discusses the clinical presentation and comprehensive management of a patient with this condition. Case Presentation: A 39-year-old female presented with a two-year history of severe burning pain, sensory loss in a